Pengembangan Media Pembelajaran Berbasis Video Animasi pada Materi Daur Hidup Hewan di Sekolah Dasar - Khasanah, Ina Rofviatun; Syachruroji, Ahmad; Nulhakim, Lukman (CV. Rayyan Dwi Bharata, 2024)
This research aims to: 1) develop animation video-based learning media on animal life cycle in elementary schools, 2) deside the possibility of animation video-based learning media on animal life cycle in elementary schools, 3) find out student respons to animation video-based learning media on animal life cycle in elementary schools. This research uses research and development (RD) using a 4D models with the step, namely define, desihn, development, disseminates. This learning media go through the stages of material expert validation test, media expert validation tests and product trials. The subjects of this research were students of class V SD Aya Sophia Islamic School as many as 20 students. Based on the the results of the research, the average validation of media experts was 47 with categories “very feasible”, material expert validation was 43,7 with categorories “very feasible”, user responses were 92,9% with the category “very good”. Thus, it can be concluded that animated videos are declared suitable for use as learning media, especially in thematic subjects.